Genetic Drivers of von Willebrand Factor Levels in an Ischemic Stroke Population and Association With Risk for Recurrent Stroke. Issue 6 (June 2017) - Williams, Stephen R.; Hsu, Fang-Chi; Keene, Keith L.; Chen, Wei-Min; Dzhivhuho, Godfrey; Rowles, Joe L.; Southerland, Andrew M.; Furie, Karen L.; Rich, Stephen S.; Worrall, Bradford B.; Sale, Michèle M.
Abstract : Background and Purpose—: von Willebrand factor (vWF) plays an important role in thrombus formation during cerebrovascular damage. We sought to investigate the potential role of circulating vWF in recurrent cerebrovascular events and identify genetic contributors to variation in vWF level in an ischemic stroke population. Methods—: We analyzed the effect of circulating vWF on risk of recurrent stroke using survival models in the VISP trial (Vitamin Intervention for Stroke Prevention) and the use of vWF in reclassification over traditional factors. We conducted a genome-wide association study) with imputation, based on 1000 Genomes Project data, for circulating vWF levels and then interrogated loci previously associated with vWF levels. We performed expression quantitative trait locus analysis for vWF across different tissues. Results—: Elevated vWF levels were associated with increased risk for recurrent stroke in VISP. Adding vWF to traditional clinical parameters also improved recurrent stroke risk prediction. We identified single-nucleotide polymorphisms significantly associated with circulating vWF at the ABO locus ( P <5×10 −8 ) and replicated findings from previous genetic associations of vWF levels in humans. Expression quantitative trait locus analyses demonstrate that most associated ABO single-nucleotide polymorphisms were also associated with vWF gene expression. Conclusions—: Elevated vWF levels are associated with recurrent stroke in VISP. In the VISP population, genetic determinants of vWF levels that impact vWF gene expression were identified. These data add to our knowledge of the pathophysiologic and genetic basis for recurrent stroke risk and may have implications for clinical care decision making. Abstract : Supplemental Digital Content is available in the text.